Beliefs about the causes of breast and colorectal cancer among women in the general population - Wang, Catharine (2009)
OBJECTIVE: To describe and compare the causal beliefs and attributions about breast and colorectal cancer among unaffected women in the general population. METHODS: A total of 439 unaffected women in the general population were recruited to complete a web-based survey assessing causal beliefs for either breast (N = 211) or colorectal cancer (N = 228). RESULTS: Heredity was ranked as the most important causal factor, followed by diet or eating habits for both cancer sites. Women endorsed the following causes of breast or colorectal cancer respectively: heredity (84.4%, 78.5%), diet or eating habits (46.4%, 69.7%), pollution in the environment (57.6%, 40.3%), aging (48.8%, 57.5%), alcohol (29.9%, 40.8%), smoking (58.3%, 50.8%), stress (27.5%, 29.4%), and lack of exercise (35.7%, 44.3%). Other factors such as prior surgery on the breast (23.7%) and colon (32.9%), or changes in one’s immune system (60.6% - breast; 59.2% - colon) were also endorsed by some women. Significant differences in the degree of endorsement for various causes of breast and colorectal cancer were identified. CONCLUSIONS: Both genetic and environmental causes for breast and colorectal cancer are endorsed by unaffected women. Misconceptions about the causes of these cancers are important targets for public education and risk communication efforts.